Synthesis of precursor of anti-cancer drugs - Abdul Jalil, Aishah; Kurono, Nobuhito; Tokuda, Masao (2004)
Highly reactive electrogenerated zinc metal (EGZn/Naph) was readily prepared by electrolysis of a DMF solution containing naphthalene and a supporting electrolyte in a one-compartment cell fitted with a platinum cathode and a zinc anode. This reactive zinc was used for efficient transformation of ethyl 2-bromoacrylate into the corresponding organozinc compound, which was reacted with various aryl halides in the presence of palladium catalyst to give the corresponding cross-coupling products, ethyl 2-arylpropenoates, in high yields. These cross-coupling reactions were successfully applied to a synthesis of the precursors of non-steroidal anti-inflammatory drugs such as ibuprofen, ketoprofen and ioxoprofen, which recently, have been shown to decrease the risk of cancer.